Sosialisasi Pengenalan Penyakit Rematik dan Makanan yang Tepat Bagi Penderita Rematik di Kelurahan Liku Lambara Tawaeli - Wirda Wirda; Reny Reny; Zulaikhah Dwi Jayanti; Nirwana Nirwana (Jurnal Nusantara Berbakti, 2023)
Rheumatic disease (rheumatoid arthritis) is a degenerative disease that affects the productive age of 25-60 years which results in decreased community productivity. The immunological pathology process occurs several years before clinical symptoms appear. One of the causes of rheumatoid arthristis is the regulation of food patterns which is a triggering factor for arthritis. The purpose of this study is to help introduce rheumatic diseases and the right food for people with rheumatism in Liku Lambara Village, Tawaeli District. The method used in the socialization was face-to-face and lecture method in one of the residents' houses. The results of the activity showed that the community understood the socialized material well. In conclusion, the community